Pharmacotherapy of Down's Syndrome: When and Which? - Tayebati, Seyed K; Cecchi, Alessandro; Martinelli, Ilenia; Carboni, Elisa; Amenta, Francesco (CNS & neurological disorders drug targets, 2019)
Down Syndrome (DS) is an essential genetic disease that involves many other body systems along with cerebral functions. The postnatal approach to treat this genetic disease includes intervention on various related disorders (e.g., heart failure, respiratory, oral, ear, and hearing disorders). However, different proposed treatments do not significantly improve the quality of life of these subjects. Another approach to the treatment of DS considering the possibility to intervene on the embryo was recently introduced. As of this, the current study has reviewed different outcomes regarding DS treatment in an animal model, namely the Ts65Dn mouse. The obtained results encouraged spending more time, efforts, and resources in this field. Besides, various treatment strategies were tried to include genetic modification, treatment with vasoactive intestinal peptide derivatives or fluoxetine. However, the main obstacle to the use of these possible treatments is the ethical issues it raises. The progression of the pregnancy in spite of awareness that DS affects the unborn and prenatal treatment of DS injured embryo are relevant dilemmas. Thus, talented researchers should spend more efforts to improve the quality of life for people affected by DS, which will allow probably a better approach to the ethical issues.